Monitoring the prevalence of thyroid disorders in the adult population of Northeast Germany - Rehman Mehmood Khattak; Till Ittermann; Matthias Nauck; Harald Below; Henry Völzke (BMC, 2016)
Abstract Background Only a few studies like ours have investigated the effect of long-term stable iodine supply on thyroid disorders in a historically iodine-deficient population, but not with a long follow-up time of 10 years. Methods Data were derived from two independent population-based cohorts of the Study of Health in Pomerania (SHIP-0 [1997-2001] and SHIP-TREND [2008-2012]) comprising 4308 and 4420 subjects, respectively. Diagnosed thyroid disorders were assessed. Thyroid gland dimensions were examined by ultrasound. Levels of serum thyrotropin (TSH) and autoantibodies to thyroperoxidase (anti-TPO Abs) were measured from blood samples. Results Median urinary iodine excretion levels decreased from 123.0 μg/l to 112.0 μg/l (p = <0.001) between 2000 and 2010. The prevalence of known thyroid disorders increased from 7.6 % [CI 6.9-8.5] to 18.9 % [CI 17.6-20.1] and of thyroid medication use from 6.2 to 11.1 %. The prevalence of goiter decreased from 35.1 to 29.4 % (p = <0.001), while the prevalence of positive anti-TPO Abs decreased from 3.9 to 2.9 % (p = 0.022). Median serum TSH levels increased from 0.69 mIU/L to 1.19 mIU/L (p = <0.001). Consequently, prevalence of high TSH (mIU/L) increased from 2.6 to 2.9 % (p = 0.452), and low TSH (mIU/L) decreased from 6.6 to 6.4 % (p = 0.737). Conclusion The decreased prevalence of iodine-deficient disorders and a stable prevalence of markers of autoimmune thyroid disorders argue for an improved iodine supply of the adult population in Northeast Germany. In contrast, the prevalence of diagnosed thyroid disorders and the intake of thyroid medication increased, although this might be related to inappropriate therapeutic decisions.